Role of Graphene-Doped Organic/Polymer Nanocomposites on the Electronic Properties of Schottky Junction Structures for Photocell Applications - Çiçek, Osman; Tan, Serhat O.; Tecimer, Hüseyin; Altındal, Şemsettin (Springer Science and Business Media LLC, 2018)
In this study, the current–voltage characteristics of non-doped and distinct graphene (Gr)-doped polyvinyl alcohol (PVA) interlayers in metal/organic polymer semiconductor type Schottky junction structures (SJSs) were investigated on both forward and reverse biases under distinct levels of illumination. The distinct doping concentration ratios (1%, 3% and 7%) of the Gr added to the PVA interlayers were compared by taking into account the basic electrical parameters, such as saturation current (Io), ideality factor (n), barrier height (ΦBo), series (Rs) and shunt resistance (Rsh). The 7% Gr-doped structure displayed the lowest Io values at zero bias. Moreover, the results indicated that the 7% Gr-doped PVA decreased the n value but increased the ΦBo value compared with values associated with structures that have different doping concentrations. In terms of quality and reliability, the Rs and Rsh values of the SJSs were obtained using Ohm’s law and Cheung’s functions, and the 7% Gr-doped structure eventually displayed more uniformly distributed and lower Rs values and the highest Rsh values. Consequently, the 7% Gr-doped structure had better overall quality because of its superior electrical properties compared with structures that have other doping concentrations. Therefore, the 7% Gr-doped structure can be used as a photodiode in electronic devices.